Personal and Contextual Contributors to Young Children's Activity-Based Perceived Self-Efficacy. Issue 4 (3rd July 2016) - Määttä, Elina; Järvelä, Sanna; Perry, Nancy
Abstract : This study investigated personal and contextual influences to young children's perceived self-efficacy (SE) in social and independent learning situations. The participants were children ( n = 24) 6–8 years old from four Finnish elementary school classrooms. First, teachers from each classroom were asked to rate their students' social competence (SC). Second, the participants were videotaped in 45 social and 15 independent learning situations, and later interviewed about their SE perceptions using video-stimulated recall. Participants with higher SE demonstrated more stable perceptions and greater involvement in social learning situations. However, a statistically significant relationship between perceived SE and SC was not found. Participants also identified 4 factors promoting perceived SE: positive emotional states, mastery experiences, personal strategic behavior, and contextual support.